Social Media and its Implementation in Higher Education - Haji Besar, Pengiran Hajah Siti Norainna bt Pengiran (Universitas Pendidikan Indonesia, 2017)
ABSTRACT: The social media comprises of diverse applications with different main functions configurations and characteristics. This paper is to gain insight into the potential use of social media in the context of higher education and particularly into the teacher use of Facebook in their teaching. The literature review presented in this paper begins by synthesizing the definition and types of social media and exploring its characteristic as well as critically interrogating related studies as to how social media, particularly Facebook, is being used in order to connect learners and support teachers teaching. It can be concluded that social media comprises of diverse applications with different main functions configurations and characteristics. The most prevalent and high profile social media is SNSs (Social Network Sites), for example Facebook, that has proved its ability to assist education through numbers of studies which show its benefits in education, but then, again at the same time, has its own drawback if it is not used effectively in an educational context. Accordingly, more studies are needed pertaining the Facebook and its implication in order to examine students-teacher interaction and studentsâ€™ engagement.KEY WORD: Social Media; Facebook; Implementation; Teachers Teaching; Higher Education.Â ABSTRAKSI: â€œMedia Sosial dan Perlaksanannya di Pengajian Tinggiâ€. Media sosial terdiri daripada pelbagai aplikasi dengan ciri-ciri utama fungsi dan konfigurasi yang berlainan. Kertas ini adalah untuk mendapatkan maklumat tentang potensi penggunaan media sosial dalam konteks pendidikan tinggi dan terutamanya penggunaan Facebook dalam pengajaran guru. Kajian literatur dalam kertas ini bermula dengan mensintesis definisi dan jenis media sosial dan meneroka ciri-cirinya secara kritikal yang berkaitan tentang bagaimana media sosial, terutamanya Facebook, digunakan dalam menyokong pengajaran guru dan pembelajaran pelajar. Dapat disimpulkan bahawa media sosial terdiri daripada pelbagai aplikasi dengan fungsi dan ciri-ciri yang berbeza. Penggunaan media sosial yang tertinggi adalah SNSs (Social Network Sites), sebagai contoh Facebook, yang telah membuktikan keupayaan untuk membantu pendidikan melalui beberapa kajian terdahulu yang mana ia menyenaraikan faedah-faedahnya dalam pengajaran dan pembelajaran, tetapi pada masa yang sama, sosial media mempunyai kelemahan sendiri jika ia tidak digunakan dengan berkesan dalam konteks pendidikan. Oleh itu, lebih banyak kajian diperlukan berkenaan dengan Facebook dan perlaksanaannya untuk mengkaji interaksi pelajar-guru dan penglibatan pelajar.KATA KUNCI: Media Sosial; Facebook; Perlaksanaan; Pengajaran Guru; Pendidikan Tinggi.About the Author: Pengiran Dr. Hajah Siti Norainna bt Pengiran Haji Besar is a Lecturer at the APB UBD (Academy of Brunei Studies, University of Brunei Darussalam), Jalan Tungku Link, BE 1410, Negara Brunei Darussalam. For academic interests, the author is able to be contacted via her e-mail address at: norainna.besar@ubd.edu.bnHow to cite this article? Haji Besar, Pengiran Hajah Siti Norainna bt Pengiran. (2017). â€œSocial Media and its Implementation in Higher Educationâ€ in MIMBAR PENDIDIKAN: Jurnal Indonesia untuk Kajian Pendidikan, Vol.2(2), September, pp.115-126. Bandung, Indonesia: UPI [Indonesia University of Education] Press, ISSN 2527-3868 (print) and 2503-457X (online). Chronicle of the article: Accepted (January 30, 2017); Revised (May 20, 2017); and Published (September 30, 2017).